Leveraging ChatGPT for Automated Assessment of Poetry Writing in Elementary Education - Nurita Hasmalani; Rustam (Didaktika: Jurnal Kependidikan, 2024)
This study aims to explore the application of artificial intelligence (AI) technology, specifically ChatGPT, in assessing poetry writing skills among students. In the digital age, using AI-based tools in education has become increasingly relevant for enhancing students' writing abilities. Through a qualitative approach, this research analyzes the effectiveness of ChatGPT in providing feedback on students' poetry, and how this technology can improve students' creativity and understanding of poetic elements. The results show that using ChatGPT as an assessment tool can aid students in refining structure, word choice, and emotional expression in poetry. This study is expected to offer new insights for educators on utilizing AI technology to enhance poetry writing instruction.